Pengaruh Persepsi, Pengetahuan Akuntansi Syariah, dan Religiusitas terhadap Minat Mahasiswa Akuntansi Berkarir di Lembaga Keuangan Syariah - Anggun Rahma Auwldhani; Dian Fitria Handayani (Jurnal Eksplorasi Akuntansi, 2023)
This research explore the impact of Shariah calculations, implications and knowledge on professional interests in Shariah financial institutions. The sample in this study is students who have taken sharia accounting courses. The type of research used in this study is quantitative approach using primary data. Primary data was obtained by distributing questionnaire directly to 100 respondents. The data was the analyzed using multiple linear regression techniques. The results of this study are (1) perception (2) Sharia accounting knowledge (3) religiosity on the interest of accounting students for a career in Sharia financial institutions.